Effectiveness of a 5-day adapted swim instruction program for children with disabilities - Carson, Tana B.; Irwin, J. Megan; Santiago Perez, Tania; Frampton, Ivana; Ruby, Lisa (Frontiers in Rehabilitation Sciences, 2025)
BackgroundDrowning is a leading cause of death for children. Some populations of children with disabilities, such as children with autism, experience a health disparity in drowning when compared to peers without disabilities.ObjectiveThis study presents a secondary data analysis of the response to intervention for a 5-day adapted swim instruction program (iCan Swim) for children with disabilities (n = 164 participants) ages 3–18 years.MethodsThis secondary data analysis assessed the effectiveness of the swim intervention on changes in swim skill level from Day 1 to Day 5. Associations between response to intervention (i.e., change score) and participant characteristics were examined using Kendall's tau-b for age and Chi-square for sex and diagnosis. Models were fit using a Poisson regression to examine potential predictors of progress across participants.ResultsSwim skills significantly improved from Day 1 (Md = 1.00, n = 164) to Day 5 (Md = 2.00, n = 164), z = −10.06, p < .001, r = .58). Most participants (61.6%) improved by at least one swim skill level. Age was weakly, yet significantly positively correlated with swim skill level change scores (τb = .154, p = .020) and was a significant predictor of swim skill level change for participants with Down Syndrome [b = .091, S.E. = .0434, p = .036, 95%CI (.006,.176)].ConclusionsWhile this 5-day adapted swim instruction program was effective for most participants in improving swim skills, certain factors may have contributed to slower progression including participant fearfulness or needing more time. Further study of these factors is warranted.